The influence of auditor independence, competence and integrity on audit quality moderated by the auditor's code of professional ethics - Hartono, Rudi; Widyastuty, Tri; Minrejo, Sumarno; Pangaribuan, David (Journal of Contemporary Accounting, 2025)
This study aims to analyze the influence of auditor independence, competence, and integrity on audit quality, as well as the role of a professional code of ethics as a moderating variable in this relationship. This study uses a quantitative method with a PLS-SEM approach. The sample consisted of 184 auditors at South Jakarta Public Accounting Firms (KAPs), selected through purposive sampling. Data were collected through questionnaires that had been tested for validity and reliability, as well as interviews with senior auditors to understand the challenges in implementing a professional code of ethics. The analysis results show that auditor independence, competence, and integrity have a positive and significant effect on audit quality, with integrity being the most dominant factor. Furthermore, a professional code of ethics has been shown to strengthen the relationship between independence, competence, and integrity with audit quality, meaning that strict implementation of a code of ethics increases effectiveness and ensures transparent and high-quality audits. However, interviews revealed challenges in implementing a code of ethics, including pressure from clients, long-term relationships that threaten independence, and a lack of training related to the code of ethics in some KAPs.